Revision of the Greater Antilles genus Paratrikona Spaeth, 1923 (Coleoptera: Chrysomelidae: Cassidinae: Dorynotini) - Simões, Marianna V. P. (Zootaxa, 2017)
The Greater Antilles genus Paratrikona is revised. One new species is described from Cuba: Paratrikona blakeae Simões new species. An updated identification key to the species of the genus and new distributional records are provided.